2014
DOI: 10.1007/s10461-014-0764-5
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use, Sexual Relationship Power, and Unprotected Sex Among Patrons in Bars and Taverns in Rural Areas of North West Province, South Africa

Abstract: We examined the relative importance of alcohol consumption and sexual relationship power (SRP) in predicting unprotected sex among 406 bar patrons in North West province, South Africa. We assessed participants' demographic characteristics, alcohol consumption, SRP, and number of unprotected sexual episodes in the past 6 months. In correlational analyses, alcohol consumption was significantly associated with frequency of unprotected sex for both males and females. SRP was significantly associated with frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Older men who had an income were much more likely to drink than younger unemployed men, and thus were probably able to purchase drinks for women and offer them transactional sex. The very strong association between transactional sex and alcohol use supports the assertion that alcohol is linked with sexual and other exchanges between men and women in this population [13, 48, 49]. In one study in Cape Town, South Africa, women with food insecurity had higher sexual risk behaviours than other women, with the associations between food and risky sex being fully mediated through women’s alcohol use [49].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Older men who had an income were much more likely to drink than younger unemployed men, and thus were probably able to purchase drinks for women and offer them transactional sex. The very strong association between transactional sex and alcohol use supports the assertion that alcohol is linked with sexual and other exchanges between men and women in this population [13, 48, 49]. In one study in Cape Town, South Africa, women with food insecurity had higher sexual risk behaviours than other women, with the associations between food and risky sex being fully mediated through women’s alcohol use [49].…”
Section: Discussionmentioning
confidence: 69%
“…Opportunities for drinking and for sexual encounters often co-exist in particular physical locations and the social dynamics that are generated in these locations [13, 53]. Patrons of drinking venues similar to those in the study site reported entering these places with an expectation of securing casual sex [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies suggest that condom use is lower in relationships in which women have less relationship power [550, 551]. Women who report lower ability to refuse sex or insist on condom use are also more likely to report being in concurrent partnerships [207, 208], which suggests an association between relationship power and concurrency.…”
Section: Discussionmentioning
confidence: 99%
“…South Africa has some of the highest levels of inequality in the world (Bond 2013); experiences some of the highest levels of violence in the world (Estes 2014); entertains endemic levels of inter-related alcohol abuse (Choi et al 2013) and bears the consequences thereof, such as rape or genderbased violence, (Wood et al 2007, Jewkes et al 2010). In addition, the country is currently battling with one of the highest burdens of HIV/AIDS in the world (SANAC 2012) and the alcohol-sex exchange is known to problematically contribute to this burden (Nkosi et al 2014). This is the empirical reality that many young people are negotiating on a daily basis.…”
Section: Introductionmentioning
confidence: 99%